THE IMPACT OF INVENTORY TURNOVER AND SALES ON NET PROFIT: (A Case Study of CV. Mulya Motor Ujung Gading, West Pasaman Regency) - Ulfah Winda; Nurlaila; Muhammad Lathief Ilhamy Nasution (Transpublika Publisher, 2022)
This study attempts to determine how Inventory Turnover and Sales influence Net Profit at CV. Mulya Motor Ujung Gading, West Pasaman Regency. This form of research is quantitative research, and the data utilized are quantitative data. Mulya Motor Ujung Gading, West Pasaman Regency's monthly financial statements serve as the source of information for this study's data collecting. Based on the sample collection undertaken using the approach of purposive sampling, a total of 36 research samples from 60 populations were acquired. In this study, descriptive statistical tests, classical assumption tests including the normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test, multiple linear regression analysis, and hypothesis testing including the t-test, F test, and the coefficient of determination were used to analyze the research sample collected between 2017-2019. The partial test results indicate that inventory turnover has a favorable and statistically significant influence on net income at CV. Mulya Motor Ujung Gading, West Pasaman Regency. CV. Mulya Motor Ujung Gading, West Pasaman Regency's sales have a positive and significant impact on net income. In addition, net income is significantly affected by the outcomes of inventory turnover and sales simultaneously.